Synthesis, photophysical properties, and photocatalytic applications of Bi doped NaTaO3 and Bi doped Na2Ta2O6 nanoparticles - Kanhere, Pushkar D. (2013)
Phase formation and photophysical properties of bismuth doped sodium tantalum oxide (perovskite, defect pyrochlore) nanoparticles prepared by a hydrothermal method were studied in detail. It was revealed that the synthesis conditions like NaOH concentration and bismuth precursor (NaBiO3·2H2O) markedly affect the crystal structure of sodium tantalum oxide. At low NaOH concentration and high bismuth precursor (NaBiO3·2H2O) content, Bi doped Na2Ta2O6 (defect pyrochlore) phase was predominantly formed, while at higher NaOH concentration, Bi doped NaTaO3 (perovskite) phase was formed. It was observed that the defect pyrochlore (Bi doped Na2Ta2O6) phase was formed and stabilized by the presence of dopant precursor (NaBiO3·2H2O). The chemical analysis of the samples confirmed the doping of Bi3+ cations in both phases. Doping of bismuth enabled visible light absorption up to 500 nm in perovskite and defect pyrochlore type sodium tantalum oxide. Bi doped NaTaO3 samples showed better performance for the photocatalytic degradation of rhodamine B than that of Bi doped Na2Ta2O6, under visible light irritation (λ>420 nm). The present results shed light on phase formation of sodium tantalate and these results are useful in understanding properties of NaTaO3 based compounds, synthesized by the hydrothermal method.